Ponatinib alleviates non-alcoholic steatohepatitis through TFEB-mediated autophagy - Lin, Zhuomiao; Yang, Meiqing; Yu, Xihui; Tan, Guozhu; Zhong, Jiahong (Frontiers in Pharmacology, 2025)
ObjectiveNon-alcoholic steatohepatitis (NASH) is a progressive liver disease with lipid accumulation, inflammation, and liver fibrosis. Ponatinib, a third-generation tyrosine kinase inhibitors for the treatment of chronic myeloid leukemia, was found to improve metabolic disorders in mice. However, the role of ponatinib in liver inflammation and fibrosis remains to be elucidated. Here we aimed to determine the effect of ponatinib in non-alcoholic steatohepatitis.MethodsWe explored the function and mechanism of ponatinib using a mouse model of NASH induced by a methionine and choline deficient (MCD) diet and LO2 cells cultured in MCD mimic medium.ResultsHere, we found that ponatinib reduced liver lipid deposition, fibrosis, and inflammation induced by MCD diet without affecting body weight and blood glucose. Meanwhile, we found that ponatinib attenuated steatohepatitis and inflammation in LO2 cells induced by MCD mimic medium. We further discovered that the expression levels of LC3II and lysosomal associated membrane protein 1 (LAMP1) were reduced and the expression level of p62 was upregulated in both mouse and cell models, suggesting that autophagy was inhibited, which was restored by ponatinib treatment. In addition, transcription factor EB (TFEB) is a major regulator of autophagy and lysosome biogenesis and the transcription and protein expression levels of TFEB were decreased in steatosis hepatocytes, which could be ameliorated by ponatinib treatment.ConclusionThese results revealed that the beneficial effects of ponatinib on NASH via TFEB-mediated autophagy.